Perencanaan Strategis Sistem Informasi Pada Universitas XYZ Menggunakan Metode Ward and Peppard - Muhammad Bayu Nugraha; Gyansar Pralebda; Renny Sari Dewi (STMIK Budi Darma, 2020)
The implementation of Information Systems (SI) and Information Technology (IT) has the aim that the performance of the University is fully effective and efficient. Information System Strategic Planning carried out by the implementation of SI and IT can provide results that are appropriate and meet the targets of XYZ University, a University that requires the effective application of IS / IT in order to improve efficiency and Human Resources that produce at XYZ University in full. By carrying out Information Systems Strategic Planning using Ward and Peppard methods can provide the results of an effective Strategic Information System Planning (ISSP) to assist the performance process at XYZ University